2019
DOI: 10.1021/acs.chemrev.8b00715
|View full text |Cite
|
Sign up to set email alerts
|

Organocobalt Complexes as Sources of Carbon-Centered Radicals for Organic and Polymer Chemistries

Abstract: Organocobalt(III) complexes (R-Co III ), defined as cobalt complexes featuring a carbon−cobalt bond, are largely used to produce carbon-centered radicals by homolytic cleavage of their C−Co bond under mild conditions. They are key compounds in cutting-edge developments in the fields of organic chemistry, biochemistry, medical research, radical reactions, and organometallic chemistry. This is the first Review of the use of R-Co III in both organic and polymer chemistries. Although pioneering works in organic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 368 publications
3
104
0
Order By: Relevance
“…7A). 89 Because of this supporting literature, alkyl-cobalt complexes have been hypothesized frequently as intermediates, beginning with seminal mechanistic work by Nishinaga on the Drago hydration. 90 Only recently, however, was a MHAT-relevant sec-alkyl cobalt salen complex characterized by 1 H NMR and implicated in a turnover-limiting transmetalation step to a nickel cocatalyst.…”
Section: Possible Roles Of Metal Alkyls In Mhat With Wf Catalystsmentioning
confidence: 99%
“…7A). 89 Because of this supporting literature, alkyl-cobalt complexes have been hypothesized frequently as intermediates, beginning with seminal mechanistic work by Nishinaga on the Drago hydration. 90 Only recently, however, was a MHAT-relevant sec-alkyl cobalt salen complex characterized by 1 H NMR and implicated in a turnover-limiting transmetalation step to a nickel cocatalyst.…”
Section: Possible Roles Of Metal Alkyls In Mhat With Wf Catalystsmentioning
confidence: 99%
“…Relative to the polar Co−O bonds, Co−C bonds tend to break homolytically to generate carbon‐based radicals as is known to occur, for instance, in the biological action of vitamin B12 . This process may be promoted by thermal treatment or by light irradiation . Recently, cobalt complexes have been used to ensure the well‐controlled polymerization of a wide variety of the challenging nonconjugated monomers through the strategy known as organometallic mediated controlled radical polymerization (OMRP) (Scheme B) .…”
Section: Introductionmentioning
confidence: 99%
“…[8] This process may be promoted by thermal treatment or by light irradiation. [9] Recently,c obalt complexes have been used to ensure the well-controlled polymerization of aw ide variety of the challenging nonconjugated monomers through the strategy known as organometallic mediated controlled radical polymerization (OMRP) (Scheme 1B). [10] Especially,F ua nd Peng et al demonstrated that an alkoxycarbonyl cobalt Salen complex (Salen is as pecific Salcyl ligand with a trans-cyclohex-diyl tether,Scheme 2) could serve as the photoinitiator as well as the mediator for visible light controlled OMRP.…”
Section: Introductionmentioning
confidence: 99%
“…[21] In turn, these high valent Co III complexes can undergo homolysis of the Co III -Alk bond, which produces an alkyl radical and regenerates Co Pc . [35] Further support for the proposal that Co Pc is capable of generating alkyl radicals in the presence of TDAE was obtained by performing an analogous radical trapping experiment using 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) as the radical acceptor instead of (dtbbpy)Ni II (o-tol)I. [36] In a similar fashion to our experiment with (dtbbpy)Ni II (o-tol)I, trapping of the benzyl radical by TEMPO is only observed in the presence of excess TDAE and catalytic amounts of Co Pc (see SI).…”
Section: Three-component Coupling Reactionsmentioning
confidence: 99%